Efficiency of selected biocide compounds in the protection of building coatings against colonization by mold fungi, cyanobacteria and algae - Kędzierski, Michał; Wiejak, Anna; Janiszewska, Jolanta; Wiśniewska, Anna; Grzywa-Niksińska, Irena; Kurzepa, Katarzyna (Polimery, 2020)
A series of biocidal compounds were evaluated as antifungal and antialgal additives for building coatings. The study comprised testing the susceptibility of coatings to colonization by Alternaria alternata, Ulocladium atrum, Aspergillus niger and Penicillium purpurogenum fungi as well as Nostoc commune cyanobacteria and Klebsormidium flaccidum green algae. White cabbage juice-based concentrate, dendrimeric peptides, peptide hydrolyzates from milk thistle and chestnut seeds, as well as selected ionic liquids, were used as additives to acrylic and silicone-based coatings. Also, some of biocidal additives were previously intercalated in montmorillonite or hydrotalcite to increase their wash-out resistance. The best results were obtained for the coatings modified with prolinate and sorbate ionic liquids added in the amount of 2 wt %. They ensure protection against the algae and cyanobacteria also after aging in water for 72 h, which indicates a possibility of their application in facade paints. Some antifungal activity was observed for the coatings containing hydrotalcite intercalated with aminododecanoic acid, while inhibition of algal growth was achieved using hydrolyzate from milk thistle seeds. However, in both cases, the coatings lost the resistance to microbial colonization when aged in water.